P018 Should NUDT genotyping be tested routinely prior to commencement of thiopurine therapy in Asian patients?. (16th January 2018) - Shah, S; Paradkar, M; Desai, D; Ashavaid, T
Abstract: Background: Thiopurines therapy remains an important armamentarium in treatment of inflammatory bowel disease (IBD). Thiopurine methyltransferase (TPMT) gene testing has not been shown as useful in Asian patients as in the caucasian patients. Recent literature indicates a strong association between a newer genetic variant, nucleoside diphosphate - linked moiety X-type motif 15 (NUDT15) and thiopurine-induced toxicity in Asian patients. We retrospectively evaluated the comparative role of TPMT genotype testing and NUDT genotype testing in IBD. Methods: As a part of routine clinical diagnostics, a total of 370 samples for TPMT genetic testing were received since 2009. Of the 370 samples received, 206 samples were available for NUDT15 genotyping. NUDT15 (C415T) and TPMT (*2, *3A, *3B, and *3C) genotyping was performed using amplification refractory mutation system–polymerase chain reaction and restriction fragment length polymorphism technique. Results were validated by DNA sequencing. Of the total samples genotyped for both TPMT and NUDT15 variants, complete medical records were available for 101 patients including their complete blood counts (CBC), thiopurine dosage as well as the incidence of leukopoenia (early or late) Results: The NUDT15 risk allele frequency was 10.7%, with the frequency of wild, heterozygous and mutant genotypes to be 80.6%, 17.5% and 1.9% respectively. TPMT variants were seen in 13/370 (3.5%) patients, whereas NUDT15 variant seen in 40/206 (19.4%) patients. Thiopurine-induced toxicity information was available for 101 patients, of which 10 developed leukopoenia and all harboured NUDT15 variant (p value <0.0001). Conclusions: NUDT 15 Genotype abnormality was more common than TPMT genotype abnormality in our patients with IBD. NUDT15 was found to be clinically more relevant than TPMT in terms of sensitivity and specificity as well as with statistically significant difference in thiopurine dose requirement for patients with NUDT15 variant. NUDT testing appears more relevant in Asian patient than TPMT testing.